2007
DOI: 10.1029/2006ja012052
|View full text |Cite
|
Sign up to set email alerts
|

Waves on the dusk flank boundary layer during very northward interplanetary magnetic field conditions: Observations and simulation

Abstract: [1] The Geotail spacecraft made an inbound passage perpendicular to the dusk equatorial magnetopause on 1 August 1998 when the interplanetary magnetic field had been very northward for more than 10 hours. As the spacecraft moved through the low-latitude boundary layer, it detected waves with $3 min period that caused transitions between cool dense magnetosheath plasma and mixed magnetosheath and magnetosphere plasmas. A region of highly fluctuating magnetic fields with variations up to 50 nT/s was observed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 64 publications
9
66
1
Order By: Relevance
“…In our endeavor to carry out these tasks, the dayside magnetosphere (magnetopause) was targeted. In the past, the magnetopause motion was reported often oscillating more or less uniformly in and out a reference position (Formisano et al, 1979) over distances of the order of 0.1 earth radii and with periods of a few minutes (Kaufmann and Konardi, 1969;Sibeck et al, 1991, Safrankova et al, 1997Haaland et al, 2004;Fairfield et al, 2007;Farrugia et al, 2008;Plaschke et al, 2009;Zhang et al, 2009). It is clear that when the parameters defining the pressure balance change, the position of the magnetopause will also vary (Semenov et al, 2002).…”
Section: Magnetic Field Lines Distribution Under Northward Imf Conditionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our endeavor to carry out these tasks, the dayside magnetosphere (magnetopause) was targeted. In the past, the magnetopause motion was reported often oscillating more or less uniformly in and out a reference position (Formisano et al, 1979) over distances of the order of 0.1 earth radii and with periods of a few minutes (Kaufmann and Konardi, 1969;Sibeck et al, 1991, Safrankova et al, 1997Haaland et al, 2004;Fairfield et al, 2007;Farrugia et al, 2008;Plaschke et al, 2009;Zhang et al, 2009). It is clear that when the parameters defining the pressure balance change, the position of the magnetopause will also vary (Semenov et al, 2002).…”
Section: Magnetic Field Lines Distribution Under Northward Imf Conditionmentioning
confidence: 99%
“…Also, it is interesting to note recent reports on formation and retreat of many X-lines at high latitudes during a steady northward IMF (Hasegawa et al, 2008;Retinò et al, 2008). From existing observations and simulations, both the KH instability and reconnection appear as acting processes in the high latitude cusp regions during northward IMF condition, yet their respective efficiency remains uncertain (Frey et al, 2003;Lavraud et al, 2006;Fairfield et al, 2007;Li et al, 2008). More generally, in past studies, the dynamic motion of the MP was mostly considered under the impact of interplanetary shocks that compress the magnetosphere (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in-situ observations from Cluster, THEMIS, Geotail, Double Star, MESSENGER, and Cassini have indicated that the KHI appears capable of generating surface waves (e.g., Fairfield et al 1990;Hasegawa et al 2004;Nykyri et al 2006;Fairfield et al 2007;Volwerk et al 2007;Taylor and Lavraud 2008;Boardsen et al 2010;Masters et al 2010;Cutler et al 2011;Hwang et al 2011bHwang et al , 2012Sundberg et al 2012). KHW have also been identified in the magnetosheath (Walker et al 2011b), the solar corona (Ofman and Thompson 2011), and the ionospheres of Mars and Venus (Pope et al 2009).…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%